Produtividade de grãos e características morfofisiológicas de arroz irrigado afetadas por local e época de semeadura - Santos, Marcos Paulo dos (2016)
The rice phenology and development are events controlled by environmental and genetic factors, and the yield potential of the crop is defined for your interaction. This study aimed to determine the environmental impacts of sites and sowing period on the morphophysiological characteristics and grain yield of contrasting lowland rice genotypes. The experiments were done in two environments, tropical, in Goianira-GO, and subtropical, Pelotas-RS, and Cachoeirinha-RS during the months of october, november, and december. The cultivars evaluated were BRS Catiana, BRS Jaçanã, BRS Pampa, BRS 7 Taim and Irga 424. The experimental design was a randomized complete block design (RBD), with four repetitions, being as factor genotype, sowing dates and sites. It was evaluated phenological development, biomass accumulation and assimilated partition, radiation use efficiency (EUR) and grain yield. In both environments, cultivars did not showed sensibility to photoperiod. The demand of degrees-day accumulated for flowering decreased for late sowing in Goianira-GO. In Cachoeirinha-RS, this trend was observed, however in a lower scale. The EUR decreased for november sowing in Goianira-GO, while in Cachoeirinha-RS there was no variation in the EUR for sowing dates from october to november. The assimilated partition do not differed among cultivars. For the subtropical environment, highest yields were observed for the period of sowing october to december. Already, in the tropical environment, occured yield decrease for sowing in november. It is probably correlated to lower values of minimum temperature accumulated during the reproductive phase. Higher accumulation of degrees-day and solar radiation in the reproductive stage and grain filling contribute to the achievement of high grain yields in the production environments in Brazil. Thus, the agroclimatic zoning has to indicate the sowing dates that optimize the accumulation degrees-day and solar radiation in these phases.